Pembinaan Pembelajaran TPQ dan MADIN Al-Amin di Desa Sukorejo dengan Menggunakan Pendekatan Langsung untuk Meningkatkan Kompetensi Guru - Stabita Hilmi, Nor Adila; Setiawan, Aris; Maghfiroh, Asmaul (Humanist Journal, 2024)
There are many sub-districts in Sukorejo, consisting of formal and non-formal institutions. One of them is TPQ and Madrasah Diniah Al Amin located in Sengkanrejo hamlet, Sukorejo village. Regent Regulation no. 21 of 2016 that Pasuruan Regency is obliged to attend Madrasah Diniah, so that each hamlet must have its own TPQ and Madrasah Diniah institutions. However, these regulations have various kinds of positive and negative impacts for students and teachers. Students who become forced during learning, causing laziness and boredom when learning takes place. In addition, seeing the conditions in the midst of the Covid19 pandemic, learning is very ineffective because teaching and learning activities are carried out online. These problems must occur in formal and non-formal educational institutions. The object in this study chose TPQ and Madin Al Amin because these institutions have very minimal competencies possessed by teachers there. Based on the condition of the minimum competence of Madin Teachers, more guidance is needed to develop their competence as a qualified and skilled educator, especially in terms of pedagogical competence. Pedagogic competence is the ability with regard to understanding students, designing and implementing learning, evaluating learning outcomes, and developing students to actualize their various potentials. For this reason, the researcher provides guidance to the Madin Teacher by using a direct approach.